Variability of Aspergillus niger after treatment with N-emthyl-N'-nitro-N-nitrosoguanidine - Musílková, M; Fencl, Z; Ujcová, E; Seichert, L (Folia microbiologica, 1978)
N-Methyl-N'-nitro-N-nitrosoguanidine influences strongly the variability of Aspergillus niger MU 90, particularly on long-term treatment. The number of spores capable of growth decreases with the duration of treatment and the number of morphological and biochemical mutants considerably increases. The highest number of mutants with increased organic acid production was obtained after a mutagenic treatment when the number of surviving spores decreased below 1%.
Keywords: Methylnitronitrosoguanidine; Spores, Fungal; spory hub; mutace; methylnitronitrosoguanidin; Mutation; Aspergillus niger